2007
DOI: 10.1021/bi700054g
|View full text |Cite
|
Sign up to set email alerts
|

Axial Ligation and Stoichiometry of Heme Centers in Adrenal Cytochromeb561

Abstract: Cytochrome (cyt) b 561 transports electrons across the membrane of chromaffin granules (CG) present in the adrenal medulla, supporting the biosynthesis of norepinephrine in the CG matrix. We have conducted a detailed characterization of cyt b 561 using electron paramagnetic resonance (EPR) and optical spectroscopy on the wild type and mutant forms of the cytochrome expressed in insect cells. The g z = 3.7 (low-potential heme) and g z = 3.1 (high-potential heme) signals were found to represent the only two auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
48
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(63 citation statements)
references
References 73 publications
9
48
2
Order By: Relevance
“…Spectrum analysis of mouse and bovine CGCytb/CYB561A1 and of TSCytb/CYB561D2 revealed the presence of two distinct, split a-bands in the spectrum of ASC-reduced proteins, which is consistent with the presence of two heme pockets (9,12,28). In Arabidopsis TCytb/CYB561B1 and mouse TSCytb/CYB561D2, singular value decomposition analysis identified two distinct b-type heme spectra that could be assigned to the two CYB561 hemes (12,16).…”
Section: Asc Reducibilitymentioning
confidence: 69%
See 2 more Smart Citations
“…Spectrum analysis of mouse and bovine CGCytb/CYB561A1 and of TSCytb/CYB561D2 revealed the presence of two distinct, split a-bands in the spectrum of ASC-reduced proteins, which is consistent with the presence of two heme pockets (9,12,28). In Arabidopsis TCytb/CYB561B1 and mouse TSCytb/CYB561D2, singular value decomposition analysis identified two distinct b-type heme spectra that could be assigned to the two CYB561 hemes (12,16).…”
Section: Asc Reducibilitymentioning
confidence: 69%
“…Western blot analysis and spectroscopy demonstrated that mutation of His residues coordinating the LP-heme (intra-vesicular-side) of Arabidopsis TCytb/ CYB561B1, and mouse CGCytb/CYB561A1, resulted in nearly undetectable protein levels. In contrast, mutations in the HPheme-coordinating residues hardly affected CYB561 expression, but resulted in altered ASC-reduction kinetics and reduced heme content (11,28,34). Somewhat contradicting results were obtained with His mutations in human DCytb/CYB561A2, and need further investigation (37,45).…”
Section: Site-directed Mutagenesismentioning
confidence: 94%
See 1 more Smart Citation
“…The positions of the b H and b L centers in the chromaffin granule membrane have been controversial, with one model assigning b H to the His88/His161 heme (as depicted in Fig. 1) (6, 7), and an earlier model assigning b H to the His54/His122 heme (8, 9). A key issue from a mechanistic perspective is whether it is b H or b L that is exposed to the cytoplasm and its pool of ascorbate.…”
mentioning
confidence: 99%
“…Cytochromes b561 are high-potential, transmembrane redox proteins of about 25 kD made of six membrane-spanning a-helices, which bind two hemes b. One heme is predicted to be close to an ascorbate binding site facing the cytosol, whereas the second heme faces the opposite side of the membrane and can be oxidized by either MDA or ferrichelates (Tsubaki et al, 1997;McKie et al, 2001;Bérczi et al, 2005;Kamensky et al, 2007). Plants contain several orthologous genes to animal cytochrome b561 Bashtovyy et al, 2003).…”
mentioning
confidence: 99%